Countermeasures and Suggestions on the Reform of Physical Education in Higher Vocational Colleges from the Perspective of Lifelong Physical Education - Li, Yongfang; Huang, Jingjing; Yuan, Yanling; Xiao, Yimei (Journal of Theory and Practice of Social Science, 2023)
With the rapid development of economy and science and technology, we media, as a technological product in the new era, is widely used in various fields in China, and is also full of people's daily life. College students are about to enter the society to participate in work, their ideological and political will inevitably be affected in the environment of we media, so how to maintain the noble moral character of college students is the task that educators in Colleges and universities should pay attention to. This paper first expounds the concept and characteristics of we media and the challenges that we media brings to the ideological and political work in Colleges and universities, and then discusses the innovation path of Ideological and political work in Colleges and Universities under the environment of we media, and puts forward personal opinions. Under the promotion of the national fitness policy in China, higher vocational college physical education also put forward relevant requirements, which requires students to master some sports knowledge and skills, but also to pay attention to their sports consciousness. Therefore, when carrying out efficient education reform, it is necessary to create teaching content based on students' lifelong sports development to lay a good foundation for their future life. When setting teaching objectives, we need to design from a long-term plan. For example, in track and field, they should make them form a good habit of jogging after supper or running in the morning every day. In this way, students can form a good habit of exercise from school, and they will not forget to exercise after graduation. In addition, after integrating the concept of lifelong sports into the physical education reform in higher vocational colleges, we should pay attention to the problem from the students' interest and acceptance, and then to the content of education, we should consider whether the students' physical and psychological development is helpful when they exercise.